Implementation of competency-based medical evaluation (cbme)-transition times: the faculty\'s appraisal of the anesthesiology curriculum for medical undergraduates using the delphi technique - Prashant Kumar; Sujata Sethi; Aarti Rohilla; Rakesh Mittal; Kiranpreet Kaur (Golestan University Of Medical Sciences, 2023)
Background: This study aimed to establish the suitability and acceptability of the curricular changes in the subject of anesthesia introduced by competency-based medical education (CBME) for undergraduate medical students. Methods: The sample consisted of 20 subject experts from different teaching institutes who were actively involved in teaching undergraduate medical students and had at least 10 years of teaching experience. The study was conducted in 3 rounds using the Delphi technique. Results: These subject experts identified the topics relevant and important to undergraduate students and also suggested the addition of role-play videos and simulations with some interesting and daring scenarios, case studies, and sessions for regional anesthesia competency. There were suggestions to include topics such as ensuring asepsis during regional anesthesia and visits to the intensive care unit (ICU). The majority of the participants were satisfied with the assessment methods. Two-thirds of the experts agreed that the anesthesia curriculum accurately covers the skills required for an Indian medical graduate. Moreover, 80% of the participants agreed that the suggested curriculum is complete and adequate for the undergraduates. Conclusion: Curricular changes introduced by CBME seem to be aligned with the goal of preparing globally relevant and socially accountable undergraduate medical students.